HUBUNGAN ADVERSITY QUOTIENT DENGAN MOTIVASI BERWIRAUSAHA PADA MAHASISWA UNIVERSITAS UDAYANA YANG MENGIKUTI PROGRAM MAHASISWA WIRAUSAHA - Wisesa, Dwitya; Indrawati, Komang Rahayu (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
PMW is one of the government initiative to support alumnus of university to be a job creator, but when college students choose to be entrepreneur surely there will be obstacles that must be overcome. Therefore need entrepreneur motivation to be up against that obstacles. One of factor which raises motivation is adversity quotient. Peoples who has adversity quotient are someone who had self motivation. College students need to have adversity quotient inside of their mind to motivate them in entrepreneurship. This research aims to know the relation between adversity quotient with entrepreneurship motivation in student of Udayana University who join PMW.This research using surfeited sample technique. The respondent in this research are students of Udayana University who join PMW with total 70 persons. Scales in this research are adversity quotient scale with total 42 items and entrepreneur motivation with total 38 items. Reliability coefficient of adversity quotient scale is 0.924 and entrepreneurship motivation is 0.941. This research used simple linear regression as additional. The result from this research showed correlation coefficient is 0.682 with probability score between variable is 0.000 which mean there are significant relation between entrepreneurship motivation variable. The coefficient determination R square is 0.465 which mean 46.5% entrepreneurship satisfaction can be explain by adversity quotient variable, however the rest 53.5% can be explain by another factor.Keywords: PMW, adversity quotient, entrepreneurship motivation